Analisis Daerah Rawan Banjir melalui Pemanfaatan Sistem Informasi Geografis (SIG) di Wilayah Kabupaten Gorontalo Provinsi Gorontalo - Ayuba, Sri Rahayu (Jurnal Ilmu Komputer (JUIK), 2023)
In the Gorontalo Disaster Risk Study 2016–2020, the main natural event that occurred in the province was a flood disaster that resulted in many lives and property casualties. Floods in the province of Gorontalo have become a common problem that occurs every year, especially during the rainy season. Reducing the risk of flood disasters that will be caused requires coordination from all parties, both the local government and the community itself. In planning the reduction of flood risk, the initial step of mapping the area vulnerable to floods can be helpful. The aim of this research is to find out the level of flooding in the district of Gorontalo. This study is a descriptive quantitative study with the methods of calculation (scoring) and overlay SIG. The spatial data used are maps of the earth, thematic maps consisting of administrative maps, elevation, rainfall, land use, soil types, river density, and the history of flooding in Gorontalo district. The data processing for this research is carried out with digital-based software called Arcgis. The results of the research obtained showed that flood-prone districts in Gorontalo district were divided into unprone areas of 74.082,95516 ha (35,02%). The fairly vulnerable area is 93,430,9777 ha (44,16%). And the highly vulnerable area amounted to 44.038,88969 ha (20,82%).